2010
DOI: 10.1002/ibd.21241
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase expression during experimental colitis in mice

Abstract: DP expression and activity are differentially regulated during DSS colitis, suggesting a pathophysiological role for these enzymes in human inflammatory bowel disease (IBD). DP inhibitors impaired neutrophil recruitment and maintenance of the Treg population during DSS-colitis, providing further preclinical evidence for the potential therapeutic use of these inhibitors in IBD. Finally, DPIV appears to play a critical role in mediating the protective effect of DP inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 59 publications
2
38
0
1
Order By: Relevance
“…After dextran sulfate sodium (DSS) treatment for 6 days to induce colitis, DPP8, but not DPP9, mRNA, and enzyme activity is elevated in the colons of both wild-type and DPPIV knockout mice (79), with inhibition of DPP activity impairing neutrophil infiltration at the site of inflammation (79). These data implicate DPP8 in the inflammatory response in colitis.…”
Section: Dpp8 and Dpp9 In The Inflammatory Responsementioning
confidence: 99%
“…After dextran sulfate sodium (DSS) treatment for 6 days to induce colitis, DPP8, but not DPP9, mRNA, and enzyme activity is elevated in the colons of both wild-type and DPPIV knockout mice (79), with inhibition of DPP activity impairing neutrophil infiltration at the site of inflammation (79). These data implicate DPP8 in the inflammatory response in colitis.…”
Section: Dpp8 and Dpp9 In The Inflammatory Responsementioning
confidence: 99%
“…Studies utilizing nonselective DP 7 inhibitors (5) and more selective DP8/DP9 inhibitors (68) have suggested an important immunological role for DP8/DP9. DP8/DP9 have also been implicated in the allergic response of the lung (9) and inflammatory bowel disorders (10). In vitro studies have demonstrated nonenzymatic roles for DP8 and DP9 in cell migration, proliferation, and apoptosis (11).…”
Section: Introductionmentioning
confidence: 99%
“…Given the beneficial effects of GLP-2, it has been studied in multiple GI diseases, including inflammatory bowel disease (IBD) and short bowel syndrome (SBS). In patients with IBD, circulating GLP-2 has been shown to be increased in patients with active disease (17), whereas animal models have found that either providing exogenous GLP-2 (18) or blocking degradation (19) reduces clinical and histological manifestations in experimental colitis. Vasoactive intestinal peptide (VIP), a secreted factor involved in intestinal motility, has been identified as the signal mediator for the anti-inflammatory actions of GLP-2 in rodent colitis models (20,21).…”
mentioning
confidence: 99%